Filmes finos de ZnSe e ZnTe obtidos por eletrodeposição para aplicação em dispositivos fotovoltaicos - Gromboni, Murilo Fernando (Universidade Federal de São Carlos, 2014)
Among the many binary semiconductors there is an increasing interest in recent decades semiconductor obtained from thin films of chalcogenides, due to its wide application in various fields of science and technology. In this class of II-VI semiconductors, cadmium selenide (CdSe), zinc selenide (ZnSe), cadmium telluride (CdTe) and zinc telluride (ZnTe) have received special attention due to its low cost and high absorption coefficient in applications for photovoltaic and photoelectrochemical cells. During this project to obtain multilayer codepósitos and techniques for electrodeposition of thin films of semiconductor ZnSe and ZnTe was studied. The electrodeposition process was studied by cyclic voltammetry analysis, which indicated that it was possible to obtain the films, which were identified as part of the anodic peak dissolutions curves, which were associated with the dissolution of the species of ZnSe and ZnTe. For the formation of multilayers from voltammetric studies defined the potentials 0.0 and - 0.5 V (vs Ag/ AgCl) for the deposition of layers of chalcogenides (Se or Te) and Zn, respectively. For the ZnSe multilayer analysis identified two morphologies SEM/EDX a smooth and globular another. The flat was associated with excess if amorphous, globular and the formation of ZnSe in the cubic phase, which was determined by XRD. Since the multilayer ZnTe showed a more crystalline structure of the ZnSe. These materials showed a large excess of chalcogenides the film and consequently a low amount of Zn, always less than 25%. However the material had high photoelectric activity, with a photo - current in the order of mA cm-³. A study was conducted to improve the crystallinity and stoichiometry of the film from heat treatment and different deposition temperatures. Certain conditions for such a condition, photovoltaic devices of the type glass\Mo\ZnSe\CdS\ZnO\ZnO:Al Glass\Mo\CZTSe\ZnTe\ZnO\ZnO:Al and Glass\Mo\ZnSe\ZnTe\ZnO\ZnO:A , the device formed by the junction CZTSe\ZnTe is presented the higher conversion efficiency and higher EOC , with a mean value of 3.34 %, and 339 mV, respectively.
Keywords: Seleneto de Zinco; Codeposição; Células fotovoltaicas; CIENCIAS EXATAS E DA TERRA::QUIMICA